2012
DOI: 10.1080/01488376.2011.645411
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Religiosity: Their Effects on Undergraduate Social Work Career Choice

Abstract: This study explores the role spirituality plays in selecting social work as a profession among 70 undergraduate students at a small private Christian college and a large state university. The relationship between spirituality and career motivation is assessed by the Abbreviated Santa Clara Strength of Religious Faith Questionnaire and student self-report of career motivations. Findings from this exploratory study indicate that more than 80% of students considered their spirituality to be influential in their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…Dat gevoel ergens toe bestemd te zijn verleent daarmee ook automatisch zingeving en bij spiritualiteit zoeken mensen dat juist. Hoewel diverse studies theoretisch onderbouwen dat er een samenhang zal zijn tussen het hebben van een roeping en het hebben van spirituele ervaringen, ontbreken daadwerkelijke cijfers hierover (Hirsbrunner, Loeffler & Rompf, 2012). Een eerste doel van onze studie is om een schatting van de sterkte van het verband te geven.…”
Section: Spiritualiteitunclassified
“…Dat gevoel ergens toe bestemd te zijn verleent daarmee ook automatisch zingeving en bij spiritualiteit zoeken mensen dat juist. Hoewel diverse studies theoretisch onderbouwen dat er een samenhang zal zijn tussen het hebben van een roeping en het hebben van spirituele ervaringen, ontbreken daadwerkelijke cijfers hierover (Hirsbrunner, Loeffler & Rompf, 2012). Een eerste doel van onze studie is om een schatting van de sterkte van het verband te geven.…”
Section: Spiritualiteitunclassified
“…Numerous examples of research exist focusing on calling as a general construct within the context of vocation (Bunderson & Thompson, ; Duffy, Bott, Allan, Torrey, & Dik, ; Duffy & Sedlacek, ; Peterson, Park, Hall, & Seligman, ). Within the helping professions, researchers have observed that students who choose to pursue a career in the helping professions often do so as a result of advocacy/social justice and some sense of calling (e.g., Duffy, Foley, et al, ; Freeman, ; Graff, ; Hirsbrunner, Loeffler, & Rompf, ; Prest et al, ).…”
Section: Work As a Calling Spirituality And Work And The Choice To mentioning
confidence: 99%
“…The connection between spirituality and work has also been discussed in the literature. There are many scholars across disciplines studying a connection between spirituality and work (see Altaf & Awan, ; Biberman & Whittey, ; Howard & Howard, ; Kahnweiler & Otte, ; Lips‐Wiersma, ; Stern & James, ), including those in the helping professions (Hirsbrunner et al, ; Prest et al, ). Within this conversation of spirituality and vocation, the concept of calling has been included, and given that the previously provided definition of calling included terms such as transcendent and summons , it is not surprising that sense of calling to a particular career has been linked to spirituality (Collins, ; Phillips, ; Terranova, ).…”
Section: Work As a Calling Spirituality And Work And The Choice To mentioning
confidence: 99%
See 1 more Smart Citation
“…Hirsbrunner, Loeffler, & Rompf, 2012;Bhagwan, 2010;Canda & Furman, 2010;Gilligan & Furness, 2006;Elkins, Lipari, & Kozora, 1999;Schafranske & Malony, 1985).…”
mentioning
confidence: 99%